Shared Moral Work of Nurses and Physicians - Storch, Janet L (Nursing ethics, 2007)
Physicians and nurses need to sustain their unique strengths and work in true collaboration, recognizing their interdependence and the complementarity of their knowledge, skills and perspectives, as well as their common moral commitments. In this article, challenges often faced by both nurses and physicians in working collaboratively are explored with a focus on the ways in which each profession's preparation for practice has differed over time, including shifts in knowledge development and codes of ethics guiding their practice. A call for envisioning their practice as shared moral work as well as practical strategies to begin that work are offered as a basis for reflection towards enhanced nurse-physician relationships.